2018
DOI: 10.1177/1035719x18804638
|View full text |Cite
|
Sign up to set email alerts
|

What would we use and how would we use it? Can digital technology be used to both enhance and evaluate well-being outcomes with highly vulnerable and disadvantaged young people?

Abstract: An increasing number of technology apps for managing wellbeing and mental health are permeating young people’s use of digital spaces. There are a range of online wellbeing tools which have been developed to promote self-tracking and build young people’s wellbeing and mental health, for example, Optimism, My Mood Tracker and Strava. Tracking outcomes of support with highly transient young people is, more broadly, a particular challenge for youth workers, evaluators and social researchers. Using digital apps to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The user-driven design approach we have adopted in this trial is intended to ensure that the intervention is engaging and relevant and reflects the experiences of YP-TASA. For example, Vichta et al [ 37 ] used interactive workshops and a web-based survey to gather YP’s perspectives on platform integration into mental health care. Venning et al [ 38 ] conducted semistructured interviews and focus groups to explore the acceptability of a low-intensity digital computer-based training platform incorporating a virtual coach with university students and HCPs.…”
Section: Discussionmentioning
confidence: 99%
“…The user-driven design approach we have adopted in this trial is intended to ensure that the intervention is engaging and relevant and reflects the experiences of YP-TASA. For example, Vichta et al [ 37 ] used interactive workshops and a web-based survey to gather YP’s perspectives on platform integration into mental health care. Venning et al [ 38 ] conducted semistructured interviews and focus groups to explore the acceptability of a low-intensity digital computer-based training platform incorporating a virtual coach with university students and HCPs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the evidence synthesis found more of a focus on adults, there was a slightly higher number of targeted strategies for young people. However, there is a need for more effective qualitative strategies such as in designing and implementing youth-oriented tailored solutions [68] and implementing a centralized DMH platform to improve stakeholder accessibility [74]. The previous review of Spadaro et al [51] suggested overhauling the application of codesign, behavior theories, and clinical evaluation.…”
Section: Secondary Findings Of Empirical Literaturementioning
confidence: 99%
“…One mixed-methods study on feasibility found DMH platforms can assist evaluating youth wellbeing [68]. However, more effective qualitative strategies are required.…”
mentioning
confidence: 99%
“…The behavioral engagement of patients with health care technologies has been associated with improved well-being [ 8 , 38 , 39 ]. As widely acknowledged in the well-being literature [ 18 ], well-being incorporates hedonic well-being, with its focus on pleasure attainment, and eudaemonic well-being, with its focus on self-realization, that is, the degree to which a person is fully functioning.…”
Section: Introductionmentioning
confidence: 99%